Health-related Quality of Life in Patients with Liver Cirrhosis: Its Determination and Correlation with Relevant Factors - Naqvi, Iftikhar Haider; Salman, Muhamad; Siddiqui, Sadia (Journal of Liaquat University of Medical & Health Sciences, 2023)
OBJECTIVE: To determine the health-related quality of life (HRQOL) among patients with Cirrhosis of the liver using a short form of liver disease quality of life (SF-LDQOL) instrument, also to correlate HRQOL scores with relevant factors. METHODOLOGY: This prospective, cross-sectional study was carried out in the medical department of Civil Hospital Karachi from May 2021 to April 2022. One hundred ninety-seven confirmed cases of Cirrhosis from either gender over 18 years of age without malignancy, HIV infection, or Psychiatric/Neurological diseases were enrolled using convenient sampling. The SF-LDQOL instrument assessed HRQOL, summarizing overall disease-targeted HRQOL (0 to 100), where a higher score shows good HRQOL or otherwise. RESULTS: Using SPSS version 23, the SF-LDQOL score was 44±7.3. The severity of liver cirrhosis by CTP-A correlated weakly (-0.1294), while CTP B and CTP C strongly correlated with SF-LDQOL scores (-0.9894 and -0.9912), respectively. The p-value for CTP A (0.705) is insignificant; however, for CTP B and C (p < 0.00001 & p < 0.00001) is significant. Demographically, the age and income status correlated strongly to SF-LDQOL scores, displaying considerable p-values (p <0.00001 and p < 0.00001). CONCLUSION: Most patients had compromised HRQOL as assessed by well-validated and more disease-specific tool SF-LDQOL score. HRQOL correlated positively with the severity of Cirrhosis by applying CTP and Model of end-stage liver disease (MELD) scoring. Sociodemographic parameters of age and income status also correlated well with HRQOL. KEYWORDS: Cirrhosis of the liver, Child Turcotte Pugh, Model of end-stage liver disease, Health-related quality of life.